2016
DOI: 10.1080/01616412.2016.1187864
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors of spontaneous hemorrhagic transformation following ischemic stroke on the initial brain CT or MRI: data from the China National Stroke Registry (CNSR)

Abstract: Spontaneous HT occurred in 0.92% of the patients with IS in the acute stage. Being female, excess alcohol consumption, atrial fibrillation, and a prolonged period between IS onset and initial imaging were associated with an increased risk of spontaneous HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Interestingly, our study found that SBP on admission was significantly lower in patients with HT (140 ± 23 mmHg) than those without HT (146 ± 23 mmHg), which is in line with some previous studies [36][37][38]. A possible explanation might be that slightly elevated blood pressure could provide an adequate cerebral blood supply, and thereby reduce the damage to blood-brain barrier due to ischemia and hypoxia [39], which may prevent the occurrence of HT.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our study found that SBP on admission was significantly lower in patients with HT (140 ± 23 mmHg) than those without HT (146 ± 23 mmHg), which is in line with some previous studies [36][37][38]. A possible explanation might be that slightly elevated blood pressure could provide an adequate cerebral blood supply, and thereby reduce the damage to blood-brain barrier due to ischemia and hypoxia [39], which may prevent the occurrence of HT.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were noted in those with ischemic stroke after thrombolysis ( 3 , 25 , 33 , 34 ). In previous studies on patients without thrombolysis, although univariate analysis showed that patients with higher NIHSS score were more prone to HT, NIHSS score was not an independent risk factor for HT ( 2 , 19 , 20 ). This is perhaps explained by the smaller sample sizes of previous studies and the fact that previous studies only investigated the relationship between HT and NIHSS score at admission rather than the relationship between sICH and NIHSS score at admission.…”
Section: Discussionmentioning
confidence: 78%
“…But this is a single-center study with only 406 patients included. Another study based on a multicenter registry analyzed sICH in those who did not receive any antithrombotic therapy ( 20 ), while most patients with acute ischemic stroke would receive antithrombotic treatment after stroke, of which approximately one third underwent antiplatelet therapy (APT) prior to the onset of stroke in the real world ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ [36][37][38] A possible explanation might be that slightly elevated blood pressure could provide an adequate cerebral blood supply, and thereby reduce the damage to blood-brain barrier due to ischemia and hypoxia,[39] which may prevent the occurrence of HT. A much-debated question is whether blood pressure is related to HT.…”
Section: Discussionmentioning
confidence: 99%